2003
DOI: 10.1002/rcm.1164
|View full text |Cite
|
Sign up to set email alerts
|

Studies on azaspiracid biotoxins. III. Instrumental validation for rapid quantification of AZA 1 in complex biological matrices

Abstract: Azaspiracids are neurotoxins produced by marine algae that have been detected in harvested mussels since 1995. They pose a significant threat to human health through the consumption of contaminated shellfish, and negatively impact the economy of areas where shellfish are harvested and processed. Regulatory agencies are beginning to advocate instrumental assays over traditional mouse bioassay methods. The development and validation of an assay method for AZA 1, the predominant azaspiracid toxin, and the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Given the specific characteristics of the instrumentation used, not all the typical fragments so far described for these compounds (Blay et al. , Lehane et al. , Krock et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the specific characteristics of the instrumentation used, not all the typical fragments so far described for these compounds (Blay et al. , Lehane et al. , Krock et al.…”
Section: Discussionmentioning
confidence: 99%
“…The LC/MS-TOF method used here provided useful information on azaspiracid-like molecules in the A. dexteroporum extracts, indicating the presence of compounds having the same atomic composition of AZA-3, AZA-7 and Compound 3. Given the specific characteristics of the instrumentation used, not all the typical fragments so far described for these compounds (Blay et al 2003, Lehane et al 2004, Krock et al 2012 were observed in the material, which deserves further analyses for a definite identification of the azaspiracid-like molecules. Particularly the presence of AZA-7 is dubious, since the molecule has so far been reported only in mussels collected in the natural environment , Lehane et al 2004) and also because of the concomitant finding of fragments belonging to other known compounds.…”
mentioning
confidence: 99%
“…A comprehensive study of the clean-up efficiencies of a range of SPE phases has been performed . Multiple tandem MS methods for AZAs have been developed using triple quadrupole instruments (Draisci et al 2000, and ion-trap instruments , Blay et al 2003. The full resolution of 11 AZAs using reversed-phase chromatography has been achieved ).…”
Section: Structural Elucidation Of Azaspiracidsmentioning
confidence: 99%
“…W ith its inherent high sensitivity, compact analyzer size, and high specificity, ion trap (IT) mass spectrometry (MS) [1] has been widely accepted for many applications, including cosmic exploration [2,3], threat and forensic detection [4,5], identification of chemical and biochemical compounds in pure form or in complex mixtures [6,7], and environmental monitoring [8,9]. Other major advantages that enhance the attractiveness of ITMS for field portable applications [10] include simple construction, relatively high pressure operation compared with other mass analyzers, low power consumption, and the ability to perform multi-stage tandem MS in a single analyzer.…”
Section: Introductionmentioning
confidence: 99%